Improved Deadbeat-Predictive Torque Control Space Vector Modulation method with Open-End Winding Interior Permanent Magnet Synchronous Motor - Yoon, Tae Yong; Lee, Hyung Woo; Lee, Kyo Beum (ICPE 2023-ECCE Asia - 11th International Conference on Power Electronics - ECCE Asia: Green World with Power Electronics, 2023)
This paper proposes an improved deadbeat-predictive torque control (DB-PTC) using space vector modulation (SVM) to drive open-end winding interior permanent magnet synchronous motor (OEW-IPMSM). Conventional predictive torque control (C-PTC) directly applies the voltage vector which closely follows the reference. Therefore, it has good transient response characteristics and simple algorithms. However, C-PTC applies the voltage vectors that have fixed magnitude in a single sampling period, which makes inconsistent switching frequency and high torque ripples. The proposed DB-PTC method selects the specific region where the virtual voltage vectors generated by the estimated reference voltage angle and cost function. Virtual voltage vectors offer to apply an optimal voltage vector, and the SVM method makes having consistent switching frequency. In result, steady state error can be decreased, the proposed method has a great advantage in terms of torque ripple reduction. The validity of proposed DB-PTC method is demonstrated through the simulation results.
Keywords: Control methods; Deadbeat; Interior permanent magnet synchronous motor; IPMSM; Open-end windings; Predictive torque controls; Space Vector Modulation; Space vector modulation method; Torque-ripple reduction; Voltage vectors; deadbeat; IPMSM; open-end winding; predictive torque control; space vector modulation; torque ripple reduction